Analisis Kemampuan Penalaran Matematis Siswa SMP dalam Menyelesaikan Soal HOTS Pada Materi Bilangan Berpangkat - Qotrunnada Salsabila; Tatang Herman; Aan Hasanah (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to describe the level of mathematical reasoning ability of junior high school students in solving HOTS problems on the material of exponents by dividing them into three categories, namely high, medium, and low. The method used in this study is descriptive qualitative. The subjects of the study consisted of 25 grade IX students at one of the State Junior High Schools in Pekanbaru. The instrument used in the study was a mathematical reasoning ability test instrument with the material of exponents of 4 HOTS questions in the form of descriptions. The data analysis techniques used in this study consisted of data reduction, data presentation, and drawing conclusions. The results showed that there were 2 students with a percentage of 8% in the high category, 20 students with a percentage of 80% in the medium category, and 3 students with a percentage of 12% in the low category. It can be concluded that the mathematical reasoning ability of grade IX students at one of Pekanbaru's junior high schools in solving HOTS problems on the material of exponents is still in the moderate category.